A radical mechanism for C–H bond cross-coupling and N2 activation catalysed by β-diketiminate iron complexes. Issue 13 (25th May 2022) - Li, Rongrong; Yang, Xinzheng; Ping, Hongming
Abstract : Density functional theory calculations and electronic structure analyses reveal a radical mechanism with spin-crossovers for C–H bond cross-coupling and N2 activation catalysed by β-diketiminate iron complexes. Abstract : Our density functional theory calculations reveal a radical mechanism for N2 fixation and conversion to N(SiMe3 )3 and PhN(SiMe3 )2 catalysed by a diketiminate-supported iron system. We found that the Na(15-crown-5)˙ radical plays an essential role as a co-catalyst in the reaction for the formation of the Me3 Si˙ radical and a stable intermediate. The attack of two Me3 Si˙ radicals to distal nitrogen and the phenyl migration to proximal nitrogen gradually weaken and activate the NN bond. The turnover-limiting step in the whole catalytic reaction is the activation of the C–H bond with a free energy barrier of 20.3 kcal mol −1 . Molecular orbital analysis of dinitrogen complexes indicates that the π back-bonding interactions between iron and N2 orbitals have major contributions to N2 fixation.